A study on awareness regarding universal precautions among medical students of tertiary teaching hospital, Bengaluru - Anuradha, Rangenahalli Vasudev; Krishnamurthy; Kaladi Anjinappa, Suhasini; Bhat, Kriti (International Journal Of Community Medicine And Public Health, 2023)
Background: Health care staffs are at increased risk of acquiring various infection as they are exposed to infectious agents at their workplace hence having awareness regarding Universal precautions help them protect themselves and provide better health care services. Methods: Descriptive study was conducted on 220 medical students of 5th, 7th and 8th term for a period of 2 months. Medical students were selected based on probability proportional to size sampling method. Semi-structured questionnaire was used to interview the study subjects Results: Assessment regarding awareness on Universal Precautions among Medical students was done by administering questionnaire on Universal Precautions. Awareness on Hand hygiene among medical students was 92% (195/220). 98.1% (208/220) of them had awareness regarding gloves usage, 45.6% (124/220) of them were unaware about safe needle practices. Conclusions: Medical students lack awareness regarding safe needle practices. They were aware of other aspects such as hand hygiene and gloves usage.